Evaluation of a push-and-pull strategy using volatiles of host and non-host plants for the management of pear psyllids in organic farming - Czarnobai De Jorge, Bruna; Koßmann, Alicia; Hummel, Hans E.; Gross, Jürgen (Frontiers in Plant Science, 2024)
Pear decline (PD) is one of the most devastating diseases of Pyrus communis in Europe and North America. It is caused by the pathogen 'Candidatus Phytoplasma pyri' and transmitted by pear psyllids (Cacopsylla pyri, C. pyricola, and C. pyrisuga). Identifying attractant and repellent volatile organic compounds (VOCs) could improve the development of alternative plant protection measurements like push-pull or attract-and-kill strategies against pear psyllids. Our objective was to investigate which chemical cues of the host plant could influence the host-seeking behavior of pear psyllids, and if cedarwood (CWO) and cinnamon bark (CBO) essential oils could serve as repellents. Based on the literature, the five most abundant VOCs from pear plants elicited EAG responses in both C. pyri and C. pyrisuga psyllid species. In Y-olfactometer trials, single compounds were not attractive to C. pyri. However, the main compound mixture was attractive to C. pyri and C. pyrisuga females. CWO and CBO were repellent against C. pyri, and when formulated into nanofibers (NF), both were repellent in olfactometer trials. However, CBO nanoformulation was ineffective in masking the odors of pear plants. In a field trial, attractive, repellent CWO and blank formulated NF were inserted in attractive green sticky traps. C. pyri captures in traps with CWO NF were statistically lower than in traps with the attractive mixture. Nevertheless, no statistical differences in the numbers of caught specimens were observed between CWO NF and those captured in green traps baited with blank NF. Transparent traps captured fewer psyllids than green ones. In a second field study with a completed different design (push-and-count design), dispensers filled with CBO were distributed within the plantation, and attractive green sticky traps were placed around the plantation. The numbers of trapped pear psyllids increased significantly in the border of thetreated plantation, showing that psyllids were repelled by the EOs in the plantation. Although further field evaluation is needed to assess and improve their effectiveness, our results show that these aromatic compounds, repellent or attractive both in nanoformulations and marking pen dispensers, offer great potential as an environmentally sustainable alternative to currently applied methods for managing pear decline vectors.